Frequency of orthopedic manifestations in COVID-19 patients. Issue 2 (April 2022) - Jacob, Roshan; Chandler, Kelly; Hagewood, Jacob; Prahad, Srihari; Sowers, Mackenzie; Naranje, Sameer
الملخص : أهداف البحث: تم سابقا رصد تأثيرات الفيروس التاجي الجديد (كوفيد-19) على الجهاز العضلي الهيكلي مع تنوع كبير. الغرض من هذه الدراسة هو تحديد مدى انتشار الأعراض العضلية الهيكلية وما إذا كانت مرتبطة بخصائص المريض الأخرى. طرق البحث: كانت هذه مراجعة بأثر رجعي لـ 685 مريضا منوما تبين أنهم مصابون بفيروس كوفيد-19 أثناء تنويمهم. استنادًا إلى استبيان كوفيد-19، سجلنا شكاوى من ظهور آلام عضلية جديدة وآلام المفاصل وآلام الظهر وضعف العضلات إضافة إلى مراجعة الرسم البياني لجميع الأمراض المصاحبة الحالية. تم إجراء التحليلات الإحصائية لتحديد العلاقة بين الأمراض المصاحبة المختلفة وأعراض العظام لمرضى كوفيد-19. النتائج: من بين 685 مريضا ثبتت إصابتهم بكوفيد-19، أظهر 186 مريضا مظهرا واحدا على الأقل من أعراض أمراض العظام (27.1٪). كان المرضى الذين عانوا من أعراض العظام أصغر بشكل ملحوظ عند 53.7 سنة مقابل 58.1 مع مؤشر كتلة جسم أعلى بكثير عند 32.6 مقابل 30.0. المرضى الذين يعانون من مرض السكري أو يعانون من السمنة كانت لديهم معدلات أعلى بشكل ملحوظ من أعراض العظام في حين أن أولئك الذين يعانون من أمراض القلب أو الرئة لديهم معدلات أقل بشكل ملحوظ. الاستنتاجات: يعاني مرضى السمنة ومرضى السكري من معدلات أعلى لأعراض العظام أثناء الإصابة بكوفيد-19. يجب إجراء المزيد من الدراسات في هذه الفئات لتحديد ما إذا كانت هذه الحالات الالتهابية أثناء العدوى لها تأثير على الجهاز العضلي الهيكلي في الأوقات المحيطة بالجراحة وبعد التعافي من العدوى. Abstract: Objectives: The effects of the novel coronavirus on the musculoskeletal system have been reported with wide variability. The purpose of this study was to determine the prevalence of musculoskeletal symptoms and if these correlated with other patient characteristics. Methods: This was a retrospective review of 685 admitted patients who were found to be positive for COVID-19 during their admission. Based on a standard COVID-19 questionnaire, we recorded complaints of new onset myalgias, joint pain, back pain, and muscle weakness and performed a chart review for all existing comorbidities. Statistical analyses were performed to determine the association between various comorbidities and orthopedic manifestations of COVID-19 patients. Results: Of the 685 patients who tested positive for COVID-19, 186 patients presented with at least one orthopedic manifestation (27.1%). Patients that experienced orthopedic manifestations were significantly younger at 53.7 years of age compared to 58.1 years of age (p = 0.003) with a significantly higher BMI (body mass index) at 32.6 versus 30.0 (p = 0.022). Patients that had diabetes or were obese had significantly higher rates of orthopedic manifestations while those that had heart or lung disease had significantly fewer. Conclusion: Obese and diabetic patients had significantly higher rates of orthopedic symptoms during COVID-19 infection. Further studies need to be carried out in these populations to determine if these comorbidities during infection have an effect on the musculoskeletal system in the perioperative setting and after recovery from infection.